2017
DOI: 10.1039/c7ta01385j
|View full text |Cite
|
Sign up to set email alerts
|

Robust fabrication of μ-patterns with tunable and durable wetting properties: hydrophilic to ultrahydrophobic via a vacuum process

Abstract: Tunable and durable lotus effect on laser-patterned stainless steel via a vacuum process in a very short time interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 44 publications
2
63
0
Order By: Relevance
“…Jagdheesh et al used a nanosecond laser light source on the stainless-steel plate to produce a single roughness micropattern. The as-prepared surface showed excellent superhydrophobicity with a roll-off angle of 5 • and a static contact angle of 180 • [15]. However, this method needs special equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Jagdheesh et al used a nanosecond laser light source on the stainless-steel plate to produce a single roughness micropattern. The as-prepared surface showed excellent superhydrophobicity with a roll-off angle of 5 • and a static contact angle of 180 • [15]. However, this method needs special equipment.…”
Section: Introductionmentioning
confidence: 99%
“…However, posterior to the hydroxylation process, the presence of water vapor molecules in the atmosphere stimulates the adsorption of a second layer of non-dissociated water molecules through the formation of hydrogen bonds with the preadsorbed hydroxyl groups present on the hydroxylated surfaces of oxides, which hinders the further adsorption of hydrocarbons, 28,36,46 since these reactive sites are passivated. Jagdheesh et al 47 reported that when using a vacuum process, lubricating oils present in the pumping mechanisms may release organic molecules into the vacuum chamber and contaminate the sample. Consequently there is a more efficient adsorption of hydrocarbons, due to the very low partial pressure of water vapor that can be reached at high vacuum.…”
mentioning
confidence: 99%
“…As for dynamics contact angle, it is indicated by sliding angle value, where low value of sliding angle shows water will slide easily on the surface as oppose to high value. It is also reported that if the value of static contact angle is > 1500 while the sliding angle below 100, the surface can be labelled as a superhydrophobic surface (Motlagh et al, 2013;Law, 2014;Jagdheesh et al, 2017Brassard et al, 2015.…”
Section: Introductionmentioning
confidence: 99%